Geochemistry of Precambrian dyke swarms in the Singhbhum craton, India: Implications for recycled crustal components in the mantle source - Manu Prasanth, M. P.; Pang, Kwan-Nang; Hari, K. R.; Sahoo, Bibhuti Bhusan; Ravindran, Arathy; Iizuka, Yoshiyuki (Frontiers in Earth Science, 2023)
The Singhbhum craton, eastern India records multiple stages of emplacement of Precambrian dyke swarms with contrasting petrogenetic models proposed for their formation. In this study, we document elemental and Sr-Nd isotopic data for three major dyke swarms in the southern part of the craton, including the ca. 2.7 Ga Ghatgaon dyke swarm, the Early Proterozoic Keonjhar dyke swarm and the ca. 1.76 Ga Pipilia dyke swarm. Dyke compositions are dominated by basalt and basaltic andesite with minor andesite, showing trace element signatures typical of continental crustal rocks. Age-corrected Nd isotopic data for Ghatgaon (εNdt = -4.8 to +4.6), Keonjhar (εNdt = -11.9 to +3.8), and Pipilia (a single sample with εNdt = -8.85) dyke swarms display substantial variations. The lack of magma compositions that could indicate the presence of elevated mantle potential temperature among the rocks suggests melting regime was likely similar to the ambient mantle. The REE systematics of the rocks indicates melting occurred between spinel-stable depths and the spinel-garnet transition zone. The dominantly mafic compositions of the rocks and ubiquitous continental crustal trace element signature are best explained by a mantle source with recycled crustal components, probably in the form of pyroxenites. Our new Nd isotopic data, which argue against any simple secular evolution trend invoked in previous studies, indicate that crustal recycling was likely an episodic phenomenon rather than a discrete, single-stage process since the Archean. Geochemical modelling indicates that a sublithospheric mantle source with minor (10% or less) recycled crustal components satisfactorily explains the trace element variations of the dyke swarms.